A imprensa periódica militar no século XIX : política e modernização no exército brasileiro (1850-1881) - Nascimento , Fernanda de Santos (2015)
The objective of this work is to understand the existence of the military periodical press during the nineteenth century, in Brazil. The military press can be defined as any form produced by military and destined invariably to the military public. So, were two specific objectives outlined: to provide data for the design of a field related to the perception of military periodical press as a source and object of research during the nineteenth century in Brazil; and understand how the discourse conveyed by the journals, especially during the Second Empire, is related to the institutionalization of national armed forces. Content analysis was the method chosen for the organization of documentary sources. Thus, it is possible to understand the existence of the military periodical press through some considerations that underlie this analysis: the military press must be understood in the process of Brazilian state of training and professionalization of the armed forces; and by the scientist character that dominated the studies during the nineteenth century. Based on these fundamental assumptions, we can infer that the drafters sought to create a positive speech, based on analogies and oppositions, during the nineteenth century, struggling to define and characterize the military class in this period. Therefore, the military press cannot be characterized as an effective political opposition space to the imperial government, but as construction space of a defining speech of military characteristics, during the nineteenth century.